POLITICAL AND SECURITY REFLECTIONS OF ALBANIAN TERRORISM ON THE REPUBLIC OF SERBIA - Petrovic, Zoran; Rašković Talović, Violeta (Serbian political thought, 2024)
The complex problem in the long history of Serbian-Albanian relations proves the complexity of Balkan history. Historically, the two neighboring nations in the Balkans, Serbian and Albanian, did not overcome their differences and conflicts and entered the 21st century together. Under the prism of understanding the political and security situation of Kosovo and Metohija, the importance of objectively looking at the development of Serbian-Albanian relations through history and determining the reasons, demands, and actions of Albanians from Kosovo and Metohija is highlighted. The author tries to descriptively show and comparatively analyze the prevalence of Albanian terrorism and the consequences of its actions in the area of Kosovo and Metohija, all in the context of the threat to the security of the Republic of Serbia and the lives of people in the area of Kosovo and Metohija. Analysis and synthesis, classic method of examination, comparative method, technique of directed interview, and scientific discussion are some of the methods used in the work. The author's goal is to point out the fact that Albanian terrorism was initiated by the desire to achieve a political goal, the idea of creating the so-called Greater Albania. As such, Albanian terrorism, at this moment, must be understood as the highest form of endangering the security of the Republic of Serbia as a whole.
Keywords: politics; political violence; security; terrorism; Albanian extremism; Serbian-Albanian relations